2014
DOI: 10.1016/j.cub.2014.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Laying Demand Induces Aversion of UV Light in Drosophila Females

Abstract: Summary Drosophila melanogaster females are highly selective about the chemosensory quality of their egg-laying sites [1–6], an important trait that promotes the survival and fitness of their offspring. How egg-laying females respond to ultraviolet light (UV) is not known, however. UV is a well-documented phototactic cue for adult Drosophila [7–13], but it is an aversive cue for larvae [14–17]. Here, we show that female flies exhibit UV aversion in response to their egg-laying demand. First, females exhibit eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 33 publications
3
56
0
1
Order By: Relevance
“…The ability to discern the changes in intensity, spectral content, timing, and exposure length of light provides valuable environmental information crucial to an organism's well-being and survival. UV lightavoidance behavior has been demonstrated in foraging larva and egg-laying activity in females (39,40). We demonstrate that the CRY/HK signaling pathway mediates UV light avoidance behavior in adult male Drosophila.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The ability to discern the changes in intensity, spectral content, timing, and exposure length of light provides valuable environmental information crucial to an organism's well-being and survival. UV lightavoidance behavior has been demonstrated in foraging larva and egg-laying activity in females (39,40). We demonstrate that the CRY/HK signaling pathway mediates UV light avoidance behavior in adult male Drosophila.…”
Section: Discussionmentioning
confidence: 69%
“…Many insects exhibit an innate spectral attraction to low-intensity UV light, as shown by phototaxis behavioral assays (36)(37)(38). In contrast, highintensity UV light induces avoidance behavior, particularly in larvae and egg-laying females (39,40), and reduces mating activity in adult male Drosophila (41).…”
Section: Cry Mediates Executive Choice Attributes Of Positive Phototamentioning
confidence: 99%
“…The adaptive significance of these behaviors remains to be determined, though reasonable hypotheses include choosing to oviposit in a place with fewer toxins, microbes, parasitoids, or large consumers, but which is near enough to the food source that larvae can find it. Regardless, initial investigation into the genes and neural circuits responsible for these behaviors illustrate the great potential to use oviposition as a model to study preferences and decision-making (Gou et al, 2014; Joseph and Heberlein, 2012; Joseph et al, 2009; Yang et al, 2008; Zhu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Previously, Chung-Hui Yang's group had found that UV avoidance emerges in Drosophila females that are in an egg-laying state (Zhu et al 2014). In an article in this issue of GENETICS, Yang and colleagues take advantage of the same behavioral paradigm to probe the functional relevance of TRPA1-mediated UV sensing and avoidance in more detail (Guntur et al 2016).…”
mentioning
confidence: 99%
“…R7 photoreceptors, expressing Rh3 and Rh4 UV-sensitive rhodopsins, play a significant role in the eye (Zhu et al 2014). Bitter GRNs in the proboscis, expressing UV-sensitive dTrpA1, do so in the taste system (Guntur et al 2016).…”
mentioning
confidence: 99%